KEUNIKAN KRISTUS DALAM PANDANGAN STEPHEN TONG - Sostenis Nggebu (STT Pelita Dunia, 2023)
Abstract: The problem of this article is the importance of recognizing the uniqueness of Christ in Stephen Tong's preaching. As a national Christian intellectual figure, Tong has traveled all over the world preaching the uniqueness of the Christ he believes in. For him, many Christians need true teaching about Christ. The purpose of this discussion leads to a description of Tong's main ideas about the uniqueness of Christ. The method used in this study is phenomenal. The result shows that Tong's thoughts about the uniqueness of Christ are firmly rooted in reformed theology. That belief became the basis for him to preach the uniqueness of Christ. Christ is God who became human to save sinners. The impact of Tong's ministry has blessed Christians, educated church members to discover the wonders of Christ and live a spiritually mature faith. In conclusion, Tong's preaching adheres to the Bible's message about the work and life of Christ. Abstrak: Problem dari artikel ini pentingnya mengenali keunikan Kristus dalam pemberitaan Stephen Tong. Sebagai tokoh intelektual Kristen nasional, Tong telah berkeliling ke berbagai penjuru dunia guna memberitakan keunikan Kristus yang diimaninya. Baginya, banyak orang Kristen membutuhkan pengajaran yang benar tentang Kristus. Tujuan pembahasan ini mengarah pada deskripsi pokok-pokok pemikiran Tong tentang keunikan Kristus. Metode yang digunakan dalam penelitian ini adalah fenomenalogis. Hasilnya, menunjukkan bahwa pemikiran Tong tentang keunikan Kristus mengakar kuat pada teologi reformed. Keyakinan itu menjadi dasar baginya untuk memberitakan keunikan Kristus. Kristus itu adalah Allah yang menjadi manusia demi menyelamatkan orang berdosa. Dampak dari pelayanan Tong telah memberkati orang Kristen, mendidik warga gereja untuk menemukan keajaiban Kristus dan menjalani iman yang dewasa secara rohani. Kesimpulannya, pemberitaan Tong patuh pada berita Alkitab tentang karya dan kehidupan Kristus.